Characteristics of Cd, Cr, Co, Cu, Fe, Mn, and Zn Heavy Metal Contents in Soils from Different Sites in Hila, Romang Island, Southwest Maluku Regency - Antho Netty Siahaya, Rahayu, Stephanie Sohilait (Lembaga Bale Literasi, 2025)
This study aims to determine the characteristics and levels of heavy metal content of Cadmium (Cd), Chromium (Cr), Cobalt (Co), Copper (Cu), Iron (Fe), Manganese (Mn), and Zinc (Zn) in soil at various locations in Hila village, Romang Island, and to evaluate its safety based on the applicable soil quality standards by comparing it with the Regulation of the Minister of Environment Number 128 of 2003, concerning Soil Quality Standards for Agricultural and Residential Activities. Sampling was carried out randomly in a stratified manner at several points representing coastal areas, lowlands, and highlands. Analysis of heavy metal content was carried out using the atomic absorption spectrophotometry method using the Atomic Absorption Spectrophotometry (AAS) atomic absorption spectrometer Buck Scientific 205 version 3.94C. The results of the study showed that the element Iron (Fe) had the highest levels compared to other elements in all sampling locations, ranging from 12,450 – 18,920 mg/kg, followed by Manganese (Mn) with a range of 320 – 680 mg/kg. Meanwhile, the element Cadmium (Cd) showed the lowest levels, which were below 0.5 mg/kg in all locations. Comparison of the measurement results with soil quality standards for agricultural and residential purposes showed that all measured heavy metal levels were still below the safe threshold, except for the elements Iron and Manganese, which had high levels but were natural conditions and not pollution. These results serve as important baseline data for environmental management and sustainable land use in Hila Village, Romang Island.